Measuring the Spirituality in Group Addiction Counselling Using Sandtray Therapy - Muhammad Farhan Mahmud; Salleh Amat; Ku Suhaila Ku Johari; Mohamad Isa Amat (Simposium Antar Bangsa Seminar dan Workshop)
The element of spirituality plays an important role in addiction counselling and recovery of an addict. The purpose of this study was to examine the differences on spirituality level before and after intervention using sandtray therapy. This study was a quasi-experimental repeated-measure design utilizing the Daily Spiritual Experience Scale (DSES). A total of 32 recovering adolescent addicts were involved in six sessions of group counselling at a government-linked drug treatment and rehabilitation facility in Malaysia. The result shows that there was a significant difference in the mean scores for pre- and post-tests. However, there was no significant difference between pre-test and post-test after having the group counselling sandtray intervention (t = -0.538, p <0.05). The discussion of findings, study implication and future direction were also discussed. This study proposes to involve the control group in a follow-up study to examine the differences on the element of spirituality between control group and treatment group.